Acellular program to develop some scouting skills to integrate blind and normal students (Scout and Guide) - Elias, Lamia Sami (International Journal of Psychosocial Rehabilitation, 2020)
Sports activities are one of the pillars that exchange experiences and knowledge, reduce routine, highlight talent and expand perceptions. It is also an effective way to train for life in order to achieve proper social adaptation, as well as building an integrated personality through the acquisition of many skills. Scouting is an important aspect of the preparation of an integrated personality of the individual because of the types of interaction that bring to the individual many of the benefits associated with the social and mental aspects and integration into society. Here came the problem of this research if the researcher wanted to know the impact of the cellular program on the development of some scouting skills in the integration between blind and normal students and the research objectives were preparing a cellular program to develop some scouting skills to integrate blind and normal students .Aim ford research was: There are statistically significant differences between the pre and post measurements in the development of some scouting skills for the blind and blind where the research methodology and field procedures included the use of the descriptive approach survey method to suit the nature of the problem and the best ways and means to reach the right results of the research and the collection of information and data required .The researcher selected a sample of (10) blind and (30) scouts and guide from the sample of our central teams of the Directorate of Education Baghdad Rusafa second and after unloading the data were statistically processed to show the impact of the cellular program.